Appropriate experimental design and pre-commercial thinning regime in Norway spruce stands on former agriculture lands in Latvia - Loks, Aksels Edgars (2020)
Recent decades Latvian land usage has change and lot of unused agricultural lands has been reforested. These areas show difference by increased growth from typical forest land, because of this trait stands need different silvicultural treatments, implementation time and intensity. Norway spruce (Picea abies) is one of the main species afforested agricultural lands, because of it growth and wood quality properties. Experimental plots were established in south east Latvia, because this region has large proportion of abandoned agricultural land afforested. One of first important silvicultural practice for managing stand development is pre-commercial thinning (PCT). It allows to alter future stands characteristics by choosing what trees will be left for future forest. PCT allows changing species composition, density and tree quality left after implementation that has direct effect on future growth. Main objective for thesis was to distinguish appropriate long-term experimental design for assessing effect of different intensity PCT on growth of future stand as well model economical outcome for each treatment. Randomized complete block design was chosen as appropriate experimental design. Four PCT-treatments were established. The treatments were 1) even distribution PCT retaining 500 trees ha-1, 2) even distribution PCT retaining 1000 trees ha-1 favoring even spatial distribution between trees, 3) PCT retaining the 1000 trees ha-1 with the largest dbh and 4) even distribution PCT with density defined from density of the plot with the lowest density before PCT (1500 trees ha-1). Economical outcome was modeled with heureca using five different scenarios that differed in number of thinnings (2,1,0) that were applied during rotation. Treatment 1500 trees ha-1 showed best economical results. It showed by 17.6% (Stand 1.) and 12% (Stand 2.) larger max NPV+LEV than closest treatment. Treatments with lower density didn’t give significant gain of lowering rotation age as well decreased economical return.